2011
DOI: 10.1097/mbc.0b013e3283468a0d
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative scanning electron microscopy analysis of fibrin networks and platelet abnormalities in diabetes

Abstract: Diabetes is a condition defined by hyperglycaemia and these patients have a high risk of thrombosis. Previous research showed that ultrastructural changes in clot formation occur in patients in whom there are changes in the coagulation system due to, for example, an inflammatory condition. In the current study, the ultrastructures of platelets and fibrin networks were investigated in 25 diabetic patients. Plasma smears, with and without the addition of thrombin, were prepared. Results indicated that the fibrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 10 publications
3
37
0
Order By: Relevance
“…A similar increase in clot matrix density and fine fiber formation was observed in PPP obtained from smokers as determined by scanning electron microscopy (SEM) [83]. Using PRP, Pretorius and colleagues demonstrated by SEM the formation of not just finer fibers, but also sheet-like matting of thrombus ultrastructure in the settings of smoking [84], type II diabetes mellitus [85] and rheumatoid arthritis [86]. Representative SEM figures of normal PRP and the preceding three conditions are represented (Fig.…”
Section: Ultrastructural Findings Supporting a Procoagulant Role For Cosupporting
confidence: 56%
See 2 more Smart Citations
“…A similar increase in clot matrix density and fine fiber formation was observed in PPP obtained from smokers as determined by scanning electron microscopy (SEM) [83]. Using PRP, Pretorius and colleagues demonstrated by SEM the formation of not just finer fibers, but also sheet-like matting of thrombus ultrastructure in the settings of smoking [84], type II diabetes mellitus [85] and rheumatoid arthritis [86]. Representative SEM figures of normal PRP and the preceding three conditions are represented (Fig.…”
Section: Ultrastructural Findings Supporting a Procoagulant Role For Cosupporting
confidence: 56%
“…Investigations of platelet poor plasma (PPP) or platelet rich plasma (PRP) obtained from samples exposed to CORM-2 [50], obtained from smokers [83,84], obtained from patients with type II diabetes mellitus [85], and rheumatoid arthritis [86] all display similar Nielsen et al 16 16 features that may be secondary to CO exposure compared to normal subject plasma.…”
Section: Ultrastructural Findings Supporting a Procoagulant Role For Comentioning
confidence: 97%
See 1 more Smart Citation
“…Their serum ferritin (range 13-28 ng/ml) and percentage of iron saturation of ferritin (range 19-33%) were within normal range. As previously presented [23,24,32], 40 ml of whole blood was collected and anticoagulated with sodium citrate (nine parts blood to one part 0.105 mol/l sodium citrate), and platelet-rich plasma (PRP) was obtained from each collected sample by centrifuging the whole blood at 1250g for 2 min.…”
Section: Methodsmentioning
confidence: 99%
“…HO-1 activity is also increased systemically in inflammatory disorders associated with thrombophilia, such as diabetes mellitus [21] and rheumatoid arthritis [22]. Critically, SEM-based investigations demonstrated that the fibrin matrix formed from blood obtained from individuals with diabetes mellitus [23] or rheumatoid arthritis [24] was very similar to that observed when normal blood was exposed to ferric chloride [2][3][4][5][6][7]. In a complementary fashion, using a viscoelastic methodology validated to detect carbon monoxide-mediated hypercoagulability in the setting of tobacco smoking [25], it was determined that a patient with a clotted ventricular assist device and hemolysis had carbon monoxide-mediated hypercoagulability, and upregulation of HO-1 was documented by increased carboxyhemoglobin concentrations [26].…”
Section: Introductionmentioning
confidence: 99%